2021
DOI: 10.3390/metabo11020079
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Receptor Blockade Increases Circulating Adiponectin Levels in People with Obesity: An Explanatory Analysis

Abstract: Human obesity is associated with decreased circulating adiponectin and elevated leptin levels. In vitro experiments and studies in high fat diet (HFD)-fed mice suggest that interleukin-6 (IL-6) may regulate adiponectin and leptin release from white adipose tissue (WAT). Herein, we aimed to investigate whether IL-6 receptor blockade affects the levels of circulating adiponectin and leptin in obese human individuals. To this end, serum samples collected during a multicenter, double-blind clinical trial were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The data on the effect of adipocyte-specific IL-6 in genetically obese (ob/ob) mice are not consistent, as studies both support 101 and undermine 103 the assertion that adipocyte IL-6 leads to insulin resistance. In humans, a recent report suggests that administration of tocilizumab in people with obesity reduces HOMA-IR 104 . In total, there is no definitive consensus on whether IL-6 from adipose tissue derived from individuals with obesity leads to insulin resistance and allocates energy to adipose tissue inflammation.…”
Section: Il-6 As An Energy Allocator In Metabolic Syndromementioning
confidence: 99%
“…The data on the effect of adipocyte-specific IL-6 in genetically obese (ob/ob) mice are not consistent, as studies both support 101 and undermine 103 the assertion that adipocyte IL-6 leads to insulin resistance. In humans, a recent report suggests that administration of tocilizumab in people with obesity reduces HOMA-IR 104 . In total, there is no definitive consensus on whether IL-6 from adipose tissue derived from individuals with obesity leads to insulin resistance and allocates energy to adipose tissue inflammation.…”
Section: Il-6 As An Energy Allocator In Metabolic Syndromementioning
confidence: 99%
“…In obesity, the IL-6 concentration increases, which decreases the sensitivity to insulin and increases glucose absorption in peripheral tissues [ 4 , 5 , 6 ], causing metabolic and cardiovascular diseases [ 7 ] and diabetes mellitus 2 [ 8 , 9 ]. Furthermore, adiponectin has been reported to increase adipocyte differentiation and inhibit IL-6 gene expression, which favors insulin sensitivity, preventing metabolic complications [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also indicate that therapeutic approaches to inhibit B cells, by reducing the levels of ACPAs anti-bodies, might provide a potential tool to control metabolic alterations induced by RA. In this sense, our longitudinal study Previous studies have demonstrated that the adipocytokine profile might be modulated by TNF-a and IL-6R inhibitors, although controversial results have been found (Derdemezis et al, 2009;Gonzalez-Gay et al, 2008Hoffman et al, 2019;Wueest et al, 2021).…”
Section: Ll Open Accessmentioning
confidence: 77%
“…Previous studies have demonstrated that the adipocytokine profile might be modulated by TNF-α and IL-6R inhibitors, although controversial results have been found ( Derdemezis et al., 2009 ; Gonzalez-Gay et al., 2008 , 2010 ; Hoffman et al., 2019 ; Wueest et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%